El reto de la prevención en la práctica odontológica (2005)
ABSTRACT: Several arguments lead to conclude that the preventive approach not only has a great potential in dental care but also implies responsibility to dental profession. Many authors have recognized that there’s a close relationship between oral and general health and emphasize the persistence of diseases that could have been prevented despite improvement in oral health status in some countries. Disease prevention is defined and its action field is delimited. An invitation is proposed in order to introduce recent concepts about both dental caries and periodontal disease, as well as risk assessment, in a new prevention perspective. Prevention is conceived as a day to day philosophy, beyond techniques, procedures and preestablished protocols.